2015
DOI: 10.1186/s13033-015-0004-z
|View full text |Cite
|
Sign up to set email alerts
|

Health system governance to support integrated mental health care in South Africa: challenges and opportunities

Abstract: Background: While South Africa has a new policy framework supporting the integration of mental health care into primary health care, this is not sufficient to ensure transformation of the health care system towards integrated primary mental health care. Health systems strengthening is needed, incorporating, inter alia, capacity building and resource inputs, as well as good governance for ensuring that the relevant policy imperatives are implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
125
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(136 citation statements)
references
References 34 publications
(60 reference statements)
4
125
0
7
Order By: Relevance
“…This may imply that there are other factors outside the health systems building blocks that should further be examined as a key contributor to health outcomes. These findings supported claims that although the health system in South Africa successfully transformed into an integrated, comprehensive national service system, many failures remain in the system burdened by the massive HIV epidemic and poor health outcomes (Chopra, Daviaud, Pattinson, Fonn, & Lawn, 2009;Coovadia, Jewkes, Barron, Sanders, & McIntyre, 2009;Kahn et al, 2007;Leon, Arana, & de Leon, 2013;D. L. Marais & Petersen, 2015;H.…”
Section: Discussionsupporting
confidence: 70%
“…This may imply that there are other factors outside the health systems building blocks that should further be examined as a key contributor to health outcomes. These findings supported claims that although the health system in South Africa successfully transformed into an integrated, comprehensive national service system, many failures remain in the system burdened by the massive HIV epidemic and poor health outcomes (Chopra, Daviaud, Pattinson, Fonn, & Lawn, 2009;Coovadia, Jewkes, Barron, Sanders, & McIntyre, 2009;Kahn et al, 2007;Leon, Arana, & de Leon, 2013;D. L. Marais & Petersen, 2015;H.…”
Section: Discussionsupporting
confidence: 70%
“…In South Africa, at the district level, mental health is specifically mentioned in the program for “Integration of mental health into PHC” and district guidelines have been developed [22]. In Nepal, the National Health Policy (1991) devolves mental health delivery to regional hospitals where specialized mental health services are provided.…”
Section: Resultsmentioning
confidence: 99%
“…[11] Furthermore, past studies have shown SA to be 'data rich but information poor' , [15] since data systems do not always provide nationally representative, good-quality information in a timely manner. [15] Capacity building to improve data collection, and making use of new digital technology, must be considered to improve implementation.…”
Section: Information and Researchmentioning
confidence: 99%
“…[13] Although political will is essential, it is necessary to involve all stakeholders when attempting any reform. [11] Vision, collaboration and oversight of the NHI will require co-operation and input from multiple levels, getting community members, service users, health workers and politicians together from the start, to share their views about the system and to commit to working together to solve problems. [13] As Bishai et al [13] explain, 'People who own the problem can anticipate the most likely social obstacles to its resolution, and their participation is essential. '…”
Section: In Practicementioning
confidence: 99%
See 1 more Smart Citation